2017
DOI: 10.3390/app7050521
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cerebellum in Unconscious and Conscious Processing of Emotions: A Review

Abstract: Abstract:Studies from the past three decades have demonstrated that there is cerebellar involvement in the emotional domain. Emotional processing in humans requires both unconscious and conscious mechanisms. A significant amount of evidence indicates that the cerebellum is one of the cerebral structures that subserve emotional processing, although conflicting data has been reported on its function in unconscious and conscious mechanisms. This review discusses the available clinical, neuroimaging, and neurophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 151 publications
(159 reference statements)
3
39
0
Order By: Relevance
“…In social/emotional cognition, patients with CB disorders show impairments in attributing facial expression to the correct emotional or mental state [106][107][108][109]; for a review, see [110]). With respect to understanding social behavior, several studies reported that CB patients have impairments in identifying or generating a plausible sequence of pictures reflecting a complex action performed by a human agent [111,112].…”
Section: Relationship To Ccas: Do Patient Outcomes Reflect Imaging Pamentioning
confidence: 99%
“…In social/emotional cognition, patients with CB disorders show impairments in attributing facial expression to the correct emotional or mental state [106][107][108][109]; for a review, see [110]). With respect to understanding social behavior, several studies reported that CB patients have impairments in identifying or generating a plausible sequence of pictures reflecting a complex action performed by a human agent [111,112].…”
Section: Relationship To Ccas: Do Patient Outcomes Reflect Imaging Pamentioning
confidence: 99%
“…The contribution of the cerebellum to implicit and explicit mechanisms underlying emotion processing has been recently acknowledged (Clausi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the cerebellum is involved in implicit aspects such as the modulation of autonomic reactions, the automatic component of emotional learning associated, e.g., with fear conditioning (Critchley et al, 2000;Sacchetti et al, 2005;Timmann et al, 2010), and in the implicit processing of emotional facial expression (Schutter et al, 2009;Clausi et al, 2017). The cerebellar vermis might play a role in this stage of emotion elaboration through its connections with the brainstem (catecholamine neurons), the hypothalamus (Snider and Maiti, 1976), and the limbic areas, such as the amygdala and hippocampus (Sacchetti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of what "emotion"-definition one follows, it is fascinating to learn about the role of the cerebellum in unconscious and conscious processing of emotions [21]. The cerebellum is normally perceived as a rather basic structure supporting skillful behavior through integrating sensory and motor information.…”
mentioning
confidence: 99%